Leadership and identities in the churches in the early second century: an interpretation of Acts 16 (Circe de clásicos y modernos, 2020)
The aim of this work is to analyze Acts 16 as a story organized by the author based on the tensions of the ἐκκλησίαι of the beginning of the IInd century. We will identify in the narrative how are represented the concerns about community leadership and the forging of a group identity. In the first case, Paul’s interac-tion with the Philippians οἶκοι leads to a reflection on the relationship between ministers and faithful. In the second, the different designations that Paul receives in the chapter would demonstrate not only the complex identity of the believers, but the community proposal of the author.
Keywords: Acts of Apostles; authority; church of Philippi; Paul of Tarsus; identity